ACTUALIZATION OF DZIGORO KANO’S JUDO PHILOSOPHY FOR VIRTUE EDUCATION IN PRESCHOOL CHILDREN - Krauze, Jekaterina; Bula-Biteniece, Inta; Ābele, Agita (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2024)
The purpose of the article: in a theoretical analysis, to substantiate the usefulness of judo martial arts philosophy in the upbringing of virtues of preschool children (5-6 years old) in judo physical activities. The article examines the historical and cultural path of judo and its philosophical aspect in the education of moral qualities following the rules and self-control, managing emotions through regulators. The problem and actuality in the 21st century is the growing aggressiveness, cruelty and emotional indifference of children revealed in sports lessons. During the discussions, it was found that children do not know what virtues are. The work of sports teachers revealed that it is possible to use the principles of judo philosophy to promote the virtues defined in regulatory documents. The conducted research revealed that Judo philosophy is useful for realizing children's intellectual potential, promoting socio-emotional development, cultivating the virtues of honesty, mutual help, respect, friendship, kindness and courage in physical activities with Judo exercises. The disciplined exercises embodied in the Judo philosophy can help promote self-discipline, self-control and endurance.